An assessment on information technology infrastructure readiness towards e-Waqf property management initiatives / Hasyeilla Abd Mutalib and Sabiroh Md Sabri - Abd Mutalib, Hasyeilla; Md Sabri, Sabiroh (Universiti Teknologi MARA, Perlis, 2021)
The implementation of Information Technology (IT) in the daily management and administration is a very crucial and essential move for every organization nowadays. The implementation of IT in a waqf institution could help to ease as well as enhances the level of efficiency and effectiveness of the management team, especially when dealing with waqf property management. Studies that, as to date, waqf institutions in Malaysia still lack in the use of IT especially in managing the waqf property. The problems often arise in waqf property management such as information of waqf property is not centralized, data are unstructured and difficulties in data retrieval which caused it to be time consuming and inefficiency in the overall waqf property management. Thus, the implementation of an information system to manage the waqf property by the waqf institution is very crucial in ensuring the competitiveness of the organization. As part of the e-Waqf property management initiative, this study was conducted to assess the waqf institution readiness towards e-Waqf property management initiatives. A qualitative method using a case study design with a semi-structured interview has been conducted with a representative from a waqf institution in Malaysia. Assessment from the elements of readiness which focus on IT infrastructure shows a good level of readiness by the top management towards the e-Waqf property management initiative. However, the systems and communication element shows a low level of readiness. Results from this study could contribute to the e-Waqf property management readiness among the waqf institution as one of the push factors that will change the way waqf property is managed in every waqf institution. Hence, this will lead to the optimally utilized of waqf property for the benefits of the Ummah in the future.